2017
DOI: 10.1016/j.jacc.2017.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting Versus Endarterectomy for Stroke Prevention

Abstract: CAS and CEA were associated with similar rates of a composite of periprocedural death, stroke, MI, or nonperiprocedural ipsilateral stroke. The risk of long-term overall stroke was significantly higher with CAS, and was mostly attributed to periprocedural minor stroke. CAS was associated with lower rates of periprocedural MI and cranial nerve palsy than CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 26 publications
2
97
1
Order By: Relevance
“…Brahmanandam et al 45 and Liu et al 46 also found CEA to be superior to CAS for periprocedural stroke or death. However, CEA has also been associated with an increased risk of periprocedural MI, 17,46 a finding consistent with our observation that CEA confers no benefit for MI. We previously conducted a meta-analysis in all carotid stenosis patients 18 and found that CAS was associated with decreased risks of periprocedural MI, hematoma, and cranial nerve palsy but with increased risks of periprocedural and long-term stroke.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Brahmanandam et al 45 and Liu et al 46 also found CEA to be superior to CAS for periprocedural stroke or death. However, CEA has also been associated with an increased risk of periprocedural MI, 17,46 a finding consistent with our observation that CEA confers no benefit for MI. We previously conducted a meta-analysis in all carotid stenosis patients 18 and found that CAS was associated with decreased risks of periprocedural MI, hematoma, and cranial nerve palsy but with increased risks of periprocedural and long-term stroke.…”
Section: Discussionsupporting
confidence: 87%
“…The Cochrane review 11 found a trend toward increased risk of periprocedural death or stroke after CAS or angioplasty (MantelHaenszel odds ratio for 3 trials: 1.71; 95% CI, 0.78-3.76), a result similar to but less precise than that reported in the present study. The inputs into a recent meta-analysis by Sardar et al 17 that considered asymptomatic patients as a subgroup analysis were similar or identical to ours, differing only when we included more studies (for any periprocedural stroke) or when Sardar et al 17 included outcomes from SAPPHIRE (for periprocedural MI) or ACT I (for long-term stroke) that we could not independently verify. Our reported results were similar to those of Sardar et al, 17 even where inputs were discrepant.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…2) However, periprocedural minor stroke may occur in most patients. 3) A study reported that the results of tailored CAS in which devices were adequately selected for high-risk patients for CEA were similar to those of CEA, with recent advances in protection procedures. 4) In particular, a proximal protection device, MOMA, has facilitated safe treatment for patients in whom CAS was previously considered to be difficult.…”
Section: Discussionmentioning
confidence: 98%